Crystal structure of 5-[4-(dimethylamino) phenyl]-3-(4-methylphenyl)-4,5- dihydro-1H-pyrazole-1-carbaldehyde - Adam, Farook; Samshuddin, Seranthimata; Ameram, Nadiah; Subramaya, Subramaya; Samartha, Laxminarayana (International Union of Crystallography, 2016)
The title compound, C19H21N3O, comprises a central pyrazole ring which is N-connected to an aldehyde group and Cconnected twice to substituted benzene rings. The pyrazole ring is twisted on the C—C single bond, and the least-squares plane through this ring forms dihedral angles of 82.44 (5) and 4.52 (5) with the (dimethylamino)benzene and p-tolyl rings, respectively. In the crystal, weak C—H O hydrogen bonds link molecules into supramolecular tubes along the b axis.